(untitled) (Journal of Medical & Health Sciences Review, 2025)
Probiotics are microorganisms, when administered in adequate amounts, provide significant health benefits to the host. Historically, ancient civilizations such as those in Egypt and India consumed probiotic-rich fermented dairy products like yogurt without understanding the microbial processes behind fermentation. Since their discovery, they have captured the interest of scientists due to their broad potential in supporting human health and disease presentation. Their influence extends across several systems. For examples they balance gut microbiota, and contribute to the integrity of the gut lining, enhance immune responses, inhibit the growth of harmful pathogens, and aid in nutrient synthesis. Modern research continues to uncover their role in managing various health conditions, including inflammatory bowel diseases, allergic disorders, metabolic imbalances, and even certain neurological and behavioral issues. Despite notable advancements, challenges remain in fully harnessing probiotics’ clinical potential. One key obstacle is the strain-specific nature of their effects. Addressing this complexity is essential for optimizing their therapeutic application. This review highlights the crucial role of probiotics as both protectors of gut health and preventive agents against a range of diseases, while also underscoring the need for continued investigation into their targeted, strain-specific functions.